A Study of Promoting Classroom Participation Based on Activities Approach - Da, Yuxia (Advances in Social Sciences Research Journal, 2016)
The study surveys learning needs of Chinese college students through the questionnaire. The results show that most B-level students get a clear understanding of their goals and make them more resourceful English learners. The research also demonstrates some students, especially the low C-level students have no definite need for English in their future goal. Faced with those challenges, the teacher is supposed to do utmost to attract their interest and participation in English by designing different activities to satisfy high level and low level students’ needs in English classroom. Therefore，some in and out- of- class activities are suggested which not only train students’ face to face communicative and cooperative competence but also make the classroom teaching more interactive.